MODERN CONCEPTS OF CLINICAL AND PATHOGENIC MECHANISMS OF COMORBIDITY OF HYPERTENSION AND IRRITABLE BOWEL SYNDROME - V. Tarasova (Bogomolets National Medical University, 2016)
Summary. The paper deals with a bibliographical review connected with comorbid course of essential hypertension and irritable bowel syndrome (IBS). GB and IBS have many common risk factors, pathogenesis, and can have a reciprocal influence on the occurrence and for course each other. The high frequency of comorbidity of GB and IBS makes it relevant to search for effective and affordable drugs for the treatment of the comorbid conditions, and the development of individualized treatment regimens in cohort of patients.